Improving Students’ Argumentative Writing Skill through Rubric and Group Feedback - Anaktototy, Karolis (Universitas Negeri Semarang, 2019)
This study intends to gain comprehensive understanding about the implementation of rubric and group feedback and to know students’ argumentative writing achievement. This study was conducted at the fourth semester students of English education study program of Teacher College Pattimura University in Ambon academic year 2015/2016. Action research method was used in this study. Data collection instruments used were students writing assessment rubrics, questionnaires, and record / field observation sheets of both observer and researcher. Descriptive statistics was used in analyzing data. The results shows that the synergy of rubric and group based feedback have improved students’ argumentative writing skills. In pre cycle the average score of the students was 66.26 while in cycle I the average score was 72.09. In cycle II the students’ average score rose to 78.00. Overall, more than 70% of the students have acquired good score for their argumentative writing. Rubric and group feedback strategy in fact has improved students’ argumentative writing skill.